Univalence criteria and quasiconformal extension of a general integral operator - Deniz, E.; Kanas, S.; Orhan, H. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.5 We give some sufficient conditions of analyticity and univalence for functions defined by an integral operator. Next, we refine the result to a quasiconformal extension criterion with the help of the Becker’s method. Further, new univalence criteria and the significant relationships with other results are given. A number of known univalence conditions would follow upon specializing the parameters involved in main results.